Comparison of Learning Outcomes Inquiry Learning Model With Cooperative Learning Model Type Number Head Together (NHT) Learning In Natural Sciences Class V In State Elementary School 66 Bengkulu City - Rohimin, Rohimin Setia; Mukti, Wiji Aziz Hari; Oktaviani, Septa; Erfan, Muhammad; Ratu, Tursina (IJIS Edu : Indonesian Journal of Integrated Science Education, 2020)
Although many have raised the Inquiry learning model and the Number Head Together (NHT) learning model, there is no research on comparison of the two models in natural science subjects. This study aims to determine whether the learning outcomes of the 5th grade science students taught using the Inquiry Learning Model is better than using the Cooperative Learning Model Number Head Together (NHT) type in SDNegeri 66 Bengkulu City. This study used two groups, namely class 5A with 31 people as the experimental group and class 5B with 31 people as the control group. This research variable consists of independent variables namely Inquiry learning model and Number Head Together (NHT) learning model while the dependent variable is the science learning outcomes. This type of research is quantitative research with Nonequivalent Control Group Design approach. Data collection techniques using observation and multiple choice test questions. Data analysis techniques using the t test. Based on the results of the study found in the posttest results of class 5A students who use Inquiry Learning Model in the medium and high categories as many as 31 students (93%) get grades of 60 to 100 while the learning outcomes of class 5B that use Cooperative Learning Models Type Number Head Together ( NHT) as many as 31 students (81%) get a value of 50 to 90. It can also be proven by the results of the t test calculation that is tcount of 4.352 and the value of the table for df = 60 with a significance level of 5% is 2,000. From the analysis it was found that tcount is greater than ttable (4.352> 2,000). The results showed that the learning outcomes of Natural Sciences 5th grade students who were taught using the Inquiry Learning Model were better than using the Cooperative Learning Model Number Head Together (NHT) type at SDN 66 Kota Bengkulu.